'I am not beholden to anyone… I consider myself to be an officer of the court': A comparison of the intermediary role in England and Wales and Northern Ireland. (April 2021) - Taggart, John
Intermediaries were first introduced by the Youth Justice and Criminal Evidence Act (1999) to facilitate communication between individuals with communication needs and the criminal justice system. Yet, despite increased academic attention into this new criminal justice actor, the content of the role remains unclear. Findings from 31 interviews with intermediaries in England and Wales and Northern Ireland as well as judges in Northern Ireland indicate that two distinct systems of intermediaries have emerged between the jurisdictions. The picture is complicated by an inequality in intermediary provision between witnesses and defendants. In England and Wales, the statutory intermediary scheme covers only witnesses whereas the 'unitary' system in Northern Ireland covers both witnesses and defendants. Drawing on the data collected, this article highlights key themes which underpin differences in intermediary practice and suggests that lessons can be learned in how we conceptualise the role and its work.